Elements of ritual and violence - Kitts, Margo (Elements in religion and violence, 2018)
Ritualized violence is by definition not haphazard or random, but seemingly intentional and often ceremonial. It has a long history in religious practice, as attested in texts and artifacts from the earliest civilizations. It is equally evident in the behaviors of some contemporary religious activists and within initiatory practices ongoing in many regions of the world. Given its longevity and cultural expanse, ritualized violence presumably exerts a pull deeply into the sociology, psychology, anthropology, theology, perhaps even ontology of its practitioners, but this is not transparent. This short volume will sketch the subject of ritualized violence, that is, it will summarize some established theories about ritual and about violence, and will ponder a handful of striking instantiations of their link